2003
DOI: 10.1161/01.str.0000058160.53040.5f
|View full text |Cite
|
Sign up to set email alerts
|

Early Outcome of Carotid Angioplasty and Stenting With and Without Cerebral Protection Devices

Abstract: Background— Carotid angioplasty and stenting (CAS) is increasingly being used for treatment of symptomatic and asymptomatic carotid artery disease (CAD). To evaluate the efficacy of cerebral protection devices in preventing thromboembolic complications during CAS, we conducted a systematic review of studies reporting on the incidence of minor stroke, major stroke, or death within 30 days after CAS. Summary of Review— … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
315
1
21

Year Published

2004
2004
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 535 publications
(349 citation statements)
references
References 74 publications
8
315
1
21
Order By: Relevance
“…13 The deployment of a stent in addition to angioplasty increases the occurrence of microembolic events as detected by transcranial Doppler sonography, 1 potentially increasing the risk of thromboembolic complications. A systematic review in 2003 found that DPD appeared to reduce the number of thromboembolic complications of CA stent placement, 10 a view that was confirmed by a review that incorporates the results of several trials that have been completed since. 22 While there seems to be an emerging consensus that CAS should only be performed with the use of DPDs, 14 data exist that points out the risks and potential adverse effects of the use of a DPD.…”
Section: Discussionmentioning
confidence: 92%
“…13 The deployment of a stent in addition to angioplasty increases the occurrence of microembolic events as detected by transcranial Doppler sonography, 1 potentially increasing the risk of thromboembolic complications. A systematic review in 2003 found that DPD appeared to reduce the number of thromboembolic complications of CA stent placement, 10 a view that was confirmed by a review that incorporates the results of several trials that have been completed since. 22 While there seems to be an emerging consensus that CAS should only be performed with the use of DPDs, 14 data exist that points out the risks and potential adverse effects of the use of a DPD.…”
Section: Discussionmentioning
confidence: 92%
“…20,25 Nevertheless, in the GSM Յ25 subset, BPDs did not seem to maintain their efficacy. It should be noted that the BPDs used in the different centers were almost exclusively distal BPDs (96% of the total), requiring the passage of the device across the lesion with the inherent risk of embolization.…”
Section: Discussionmentioning
confidence: 98%
“…[259][260][261][262] Contrast-induced nephropathy has been reported in <1% of cases, because CAS is generally avoided in patients with severe renal dysfunction. 263 The results of observational studies suggest that EPDs reduce rates of adverse events during CAS [264][265][266] when operators are experienced with the apparatus 56 ; in unfamiliar hands, the devices are associated with worse clinical outcomes 67,178,180 and a higher rate of stroke. 267 …”
Section: Carotid Artery Stentingmentioning
confidence: 99%